Family characteristics and income: Evidence from Indonesia - Husban Yarjuna Firdaus; Aham Bagas Satrio; Muhammad Safli Fahrudin; Muhammad Adam Siregar (Sebelas Maret Business Review, 2023)
Balance in the form of linkages between socioeconomic aspects of a region is the key to economic stability. This economic stability is essential to achieve community welfare, so existing interventions must be considered considering that  a slight change in one aspect will affect the economic balance. With the achievement of community welfare, the economic development of a region can be said to be good, which also has implications for handling existing socioeconomic problems. However, the misalignment of education level, gender, internet access, and marital status of each district/city area triggers differences in income levels. Therefore, through this study, it is expected to be able to answer whether factors such as education level, gender, internet access, and marital status are factors that influence the magnitude of income levels, especially in DIY Provinces. By using IFLS-5 data processed through an estimat ion method using logistic regression, test results were obtained that gender and internet access factors significantly affected the amount of people's income. In contrast, the level of education and marital status did not significantly affect the income of people in DIY Province